Interaction between indigenous hydrocarbon-degrading bacteria in reconstituted mixtures for remediation of weathered oil in soil - Nasser Al-Kaabi (17347018) (2022)
It has been demonstrated that biostimulation is necessary to investigate the interactions between indigenous bacteria and establish an approach for the bioremediation of soils contaminated with weathered oil. This was achieved by adjusting the carbon (C)/nitrogen (N)/phosphorus (P) ratio to 100/10/1 combined with the application of 0.8 mL/kg Tween-80. In addition, three indigenous bacteria isolated from the same soil were introduced solely or combined concomitantly with stimulation. Removal of n-alkanes and the ratios of n-heptadecane to pristane and n-octadecane to phytane were taken to indicate their biodegradation performance over a period of 16 weeks. One strain of Pseudomonas aeruginosa D7S1 improved the efficiency of the process of stimulation. However, another Pseudomonas aeruginosa, D5D1, inhibited the overall process when combined with other bacteria. One strain of Bacillus licheniformis D1D2 did not affect the process significantly. The Fourier transform infrared analysis of the residual hydrocarbons supported the conclusions pertaining to the biodegradation processes when probing the modifications in densities and stretching. The indigenous bacteria cannot mutually benefit from their metabolisms for bioremediation if augmented artificially. However, the strain Pseudomonas. aeruginosa D7S1 was able to perform better alone than in a consortium of indigenous bacteria. Other Information Published in: Biotechnology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.btre.2022.e00767